Maximising follow-up participation rates in a large scale 45 and Up Study in Australia. Issue 1 (December 2016) - Bauman, Adrian; Phongsavan, Philayrath; Cowle, Alison; Banks, Emily; Jorm, Louisa; Rogers, Kris; Jalaludin, Bin; Grunseit, Anne
Abstract Background The issue of poor response rates to population surveys has existed for some decades, but few studies have explored methods to improve the response rate in follow-up population cohort studies. Methods A sample of 100, 000 adults from the 45 and Up Study, a large population cohort in Australia, were followed up 3.5 years after the baseline cohort was assembled. A pilot mail-out of 5000 surveys produced a response rate of only 41.7 %. This study tested methods of enhancing response rate, with three groups of 1000 each allocated to (1) receiving an advance notice postcard followed by a questionnaire, (2) receiving a questionnaire and then follow-up reminder letter, and (3) both these strategies. Results The enhanced strategies all produced an improved response rate compared to the pilot, with a resulting mean response rate of 53.7 %. Highest response was found when both the postcard and questionnaire reminder were used (56.4 %) but this was only significantly higher when compared to postcard alone (50.5 %) but not reminder alone (54.1 %). The combined approach was used for recruitment among the remaining 92, 000 participants, with a resultant further increased response rate of 61.6 %. Conclusions Survey prompting with a postcard and a reminder follow-up questionnaire, applied separately or combined can enhance follow-up rates in large scale survey-based epidemiological studies.